2018
DOI: 10.1097/cej.0000000000000394
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and prostate tissue distribution of metformin in a preprostatectomy prostate cancer cohort

Abstract: Metformin has recently been shown to have potential to reduce prostate cancer risk. We conducted a randomized, double-blind, placebo-controlled trial to determine the modulating effects of metformin on tissue and systemic biomarkers of drug activity and its distribution into the prostate tissue. Twenty patients with prostate cancer scheduled to undergo prostatectomy were randomly assigned to receive either extended-release metformin or placebo for a median of 34 days before surgery. Prostatectomy and serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…However, important issues and concerns about this off-label activity are still unsolved. In particular, extremely high drug concentrations (within the mM range) are required to induce antitumor effects in in vitro studies, although in vivo metformin intratumoral concentrations were reported to be several fold higher than in plasma ( Nguyen et al, 2017 ; Baldassari et al, 2018 ). It was therefore proposed that protracted in vivo treatment using clinically reachable doses, can possibly induce antitumor effects ( Gritti et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, important issues and concerns about this off-label activity are still unsolved. In particular, extremely high drug concentrations (within the mM range) are required to induce antitumor effects in in vitro studies, although in vivo metformin intratumoral concentrations were reported to be several fold higher than in plasma ( Nguyen et al, 2017 ; Baldassari et al, 2018 ). It was therefore proposed that protracted in vivo treatment using clinically reachable doses, can possibly induce antitumor effects ( Gritti et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a pre-prostatectomy study of human prostate cancer patients, the serum and prostate tissue concentration of metformin was determined. After 4–12 weeks of daily administration, serum concentrations increased from undetectable to 3.6 μg/mL, and prostate tissue concentrations of 0.88 to 51.2 μg/g were measured [ 83 ]. The observed pharmacokinetics of metformin in dogs seemed to be comparable to the pharmacokinetics reported for cats and humans [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum and saliva metformin concentrations were measured using high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS; ref. 48 ). Briefly, an aliquot of serum or saliva was mixed with the internal standard, phenformin.…”
Section: Methodsmentioning
confidence: 99%